Studies on Co(II) Thiosemicarbazone Adducts with 2-Pyridine Ethanol and 2,2´ -Bipyridyl - K. Agrawal, Suresh; Chand, Subhash (Asian Journal of Chemistry, 2010)
The adducts of thiosemicarbazones of 2,5-dimethoxy phenyl glyoxal, 2-hydroxy-5-carboxy acetophenone and Co(II) phenyl thiosemicarbazone of resacetophenone with 2-pyridine ethanol and 2,2´-bipyridyl with the composition (CoLL´Cl2H2O), (CoLL"Cl2H2O), CoLL´ClH2O)2 and CoLL"Cl(H2O)2, where L═thiosemicarbazone and L´═ 2-py. ethanol and L"═2,2´-bipy., have been prepared. The adducts have been characterised on the basis of magnetic and spectral studies. Conductance values in DMF showed them to be non-electrolytes.